Trade-offs in ecosystem impacts from nanomaterial versus organic chemical ultraviolet filters in sunscreens. (1st August 2018) - Hanigan, David; Truong, Lisa; Schoepf, Jared; Nosaka, Takayuki; Mulchandani, Anjali; Tanguay, Robert L.; Westerhoff, Paul
Abstract: Both nanoparticulate (nZnO and nTiO2 ) and organic chemical ultraviolet (UV) filters are active ingredients in sunscreen and protect against skin cancer, but limited research exists on the environmental effects of sunscreen release into aquatic systems. To examine the trade-offs of incorporating nanoparticles (NPs) into sunscreens over the past two decades, we targeted endpoints sensitive to the potential risks of different UV filters: solar reactive oxygen production in water and disruption of zebrafish embryo development. First, we developed methodology to extract nanoparticles from sunscreens with organic solvents. Zebrafish embryos exposed to parts-per-million NPs used in sunscreens displayed limited toxicological effects; nZnO particles appeared to be slightly more toxic than nTiO2 at the highest concentrations. In contrast, seven organic UV filters did not affect zebrafish embryogenesis at or near aqueous solubility. Second, to simulate potent photo-initiated reactions upon release into water, we examined methylene blue (MB) degradation under UV light. nTiO2 from sunscreen caused 10 times faster MB loss than nZnO and approached the photocatalytic degradation rate of a commercial nTiO2 photocatalysts (P25). Organic UV filters did not cause measurable MB degradation. Finally, we estimated that between 1 and 10 ppm of sunscreen NPs in surface waters could produce similar steady state hydroxyl radical concentrations as naturally occurring fluvic acids under sunlight irradiation. Incorporation of NPs into sunscreen may increase environmental concentrations of reactive oxygen, albeit to a limited extent, which can influence transformation of dissolved substances and potentially affect ecosystem processes. Graphical abstract: Highlights: Method developed to extract nanoscale Ti and Zn oxides from sunscreens. Extracted TiO2 and ZnO sunscreen particles oxidized methylene blue under UV light. Zebrafish embryogenesis was weakly perturbed by nanoparticles from sunscreens. Organic UV filters did not oxidize methylene blue or perturb zebrafish embryogenesis. Environmental trade-offs exist between organic and inorganic UV filter.